2015
DOI: 10.1159/000441276
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Early Metabolic Left Ventricular Remodeling in Systemic Hypertension

Abstract: Objectives: Hypertension (HTN) is a common cause of left ventricular hypertrophy (LVH). Sustained pressure overload induces a permanent myocardial switch from fatty-acid to glucose metabolism. In this study, we tested the hypothesis that metabolic remodeling, characterized by increased myocardial glucose uptake, precedes structural and functional remodeling in HTN-induced LVH. Methods: We recruited 31 patients: 11 with HTN only, 9 with HTN and LVH and 11 normotensive controls without LVH. Transthoracic echocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Cardiac positron emission tomography (PET) imaging studies have revealed an increase in fatty acid uptake and a decrease in glucose uptake oxidation with increasing severity of DD. [21][22][23] This is different from the greater glucose oxidation seen in HFrEF. However, the excess fatty acid oxidation in HFpEF may lead to overburdening of the mitochondria, accumulation of acylcarnitines, and greater oxidative stress.…”
Section: Metabolic Adaptation Versus Maladaptationmentioning
confidence: 84%
“…Cardiac positron emission tomography (PET) imaging studies have revealed an increase in fatty acid uptake and a decrease in glucose uptake oxidation with increasing severity of DD. [21][22][23] This is different from the greater glucose oxidation seen in HFrEF. However, the excess fatty acid oxidation in HFpEF may lead to overburdening of the mitochondria, accumulation of acylcarnitines, and greater oxidative stress.…”
Section: Metabolic Adaptation Versus Maladaptationmentioning
confidence: 84%
“…For example, to assess glucose uptake, the myocardial rate of 18 F-FDG uptake can be measured as K i (mL/min/g) using PET imaging. 23 However, since FDG is 2-deoxy glucose, it does not undergo glycolysis and is not oxidized the same as glucose.…”
Section: Assessment Of Substrate Changesmentioning
confidence: 99%
“…Although the metabolic changes in HFpEF are not well defined, some studies in humans indicated that, contrary to HFrEF, there may be decreased myocardial glucose uptake in diastolic dysfunction (DD) and diabetic cardiomyopathy. 23,26 HFpEF is closely associated with insulin resistance, therefore it remains to be determined whether the decrease in glucose uptake was due to the associated insulin resistance. It is thought that greater dependence on fatty acids and reduced glucose uptake due to insulin resistance may lead to overburdening the mitochondria, accumulation of acylcarnitines, mitochondrial uncoupling, and production of reactive oxygen species primarily at the levels of complexes I and III of the respiratory chain.…”
Section: Metabolic Alterations In Diastolic Dysfunctionmentioning
confidence: 99%
“…Moving beyond genetic variation, the identification of individual metabolic phenotypes utilizing laboratory diagnostics and molecular imaging offers the opportunity to apply precision medicine to cardiovascular disease. The paper published in this issue of Cardiology by Hamirani et al [3] presents evidence that supports the application of precision metabolic medicine using noninvasive monitoring to identify subtypes and detect progression to hypertension-associated cardiomyopathy.…”
mentioning
confidence: 98%
“…This, in contrast to point-in-time assessments with snap-frozen tissue or serum samples, allows for initial and temporal flux quantifications in vivo. Examples would include the ability to monitor changes in carbohydrate uptake as reported in this issue by Hamirani et al [3], as well as assessments of myocardial oxygen uptake, lactate utilization, and fatty acid metabolism in ischemic and failing heart conditions. Monitoring for heart transplant-associated metabolic cardiac stress might represent another potential application.…”
mentioning
confidence: 99%